The role of cell-mediated immunity against influenza and its implications for vaccine evaluation - Janssens, Yorick; Joye, Jasper; Waerlop, Gwenn; Clement, Frédéric; Leroux-Roels, Geert; Leroux-Roels, Isabel (Frontiers in Immunology, 2022)
Influenza vaccines remain the most effective tools to prevent flu and its complications. Trivalent or quadrivalent inactivated influenza vaccines primarily elicit antibodies towards haemagglutinin and neuraminidase. These vaccines fail to induce high protective efficacy, in particular in older adults and immunocompromised individuals and require annual updates to keep up with evolving influenza strains (antigenic drift). Vaccine efficacy declines when there is a mismatch between its content and circulating strains. Current correlates of protection are merely based on serological parameters determined by haemagglutination inhibition or single radial haemolysis assays. However, there is ample evidence showing that these serological correlates of protection can both over- or underestimate the protective efficacy of influenza vaccines. Next-generation universal influenza vaccines that induce cross-reactive cellular immune responses (CD4+ and/or CD8+ T-cell responses) against conserved epitopes may overcome some of the shortcomings of the current inactivated vaccines by eliciting broader protection that lasts for several influenza seasons and potentially enhances pandemic preparedness. Assessment of cellular immune responses in clinical trials that evaluate the immunogenicity of these new generation vaccines is thus of utmost importance. Moreover, studies are needed to examine whether these cross-reactive cellular immune responses can be considered as new or complementary correlates of protection in the evaluation of traditional and next-generation influenza vaccines. An overview of the assays that can be applied to measure cell-mediated immune responses to influenza with their strengths and weaknesses is provided here.